Using bio-inspired approaches to improve the quality of service in a multicast routing. (2017) - Mahseur, Mohammed; Boukra, Abdelmadjid
This paper deals with the problem optimising the quality of service (QoS) in a multicast routing with multiple constraints (multi constrained least-cost multicast routing problem). To solve this problem, we propose two approaches. The first one named biogeography-based optimisation (BBO) is inspired by the biogeography mathematics; the second, named bat algorithm (BA) is inspired from bat behaviour. We propose to use a tree structure to represent the solution. We start optimising the graph representing the network. We propose to generate the initial population with greedy heuristic using depth first search (DFS). Then, we optimise the initial population solutions in order to minimise the execution time. We have adapted BBO and BA operators to deal with the discrete nature of the problem and the structures representing the problem solution. In experiments, we have used Waxman topology model to generate the graph. The results were encouraging in comparison with other existing algorithms.